ChemInform Abstract: New Thiostannates Synthesized under Solvothermal Conditions: Crystal Structures of (trenH)2Sn3S7 and {[Mn(tren)]2Sn2S6}. Issue 3 (22nd January 2013) - Pienack, Nicole; Schinkel, Diana; Puls, Angela; Ordolff, Marie‐Eve; Luehmann, Henning; Naether, Christian; Bensch, Wolfgang
Abstract The new compounds (II) and (IV) are solvothermally synthesized and their crystal structures are determined by single crystal XRD.